Frat Daddies and Sorostitutes: How TotalFratMove.com and Greek Identity Influence Greek Students' Rape Myth Acceptance. (20th December 2016) - Thompson, Bailey A.; Ortiz, Rebecca R.
College students in social Greek organizations are at greater risk of sexual assault than other college students. The present study examined how readership of the online news siteTotalFratMove.com (TFM), through a survey questionnaire, which often includes coverage of stereotypical fraternity culture, may impact rape myth acceptance. Results revealed that the more frequently Greeks read TFM, the more likely they were to be accepting of rape myths when also taking into account the strength of their Greek social identity. Challenging stereotypes of the "frat daddy" and "sorostitite" may indirectly challenge behaviors and attitudes associated with rape myth acceptance otherwise perpetuated by Greek culture.Public Health Significance Statement: This study suggests that the more frequently Greek-affiliated college students read the popular website TFM, the more likely they were to have rape myth supportive attitudes when they also felt like being Greek was an integral part of their identity.